Europium(III)‐Doped MgAl2O4 Spinel Nanophosphor Prepared by CO2 Laser Co‐Vaporization. Issue 8 (29th June 2016) - Wenisch, Christoph; Kurland, Heinz‐Dieter; Grabow, Janet; Müller, Frank A.
Abstract : Photoluminescent nanoparticles (NPs) are of specific interest for biomedical applications, bioimaging, and cell tracking. Here, we report on the synthesis of europium(III)‐doped MgAl2 O4 spinel NPs by the CO2 laser co‐vaporization of a homogeneous raw powder mixture consisting of micrometer‐sized MgAl2 O4 and Eu2 O3 (2 and 4 mol%, respectively). The resulting NPs are spherically shaped, show a narrow size distribution (mean diameter: ~30 nm), and are well dispersed. The as‐prepared NPs are highly crystalline and consist of MgAl2 O4 with small amounts of the secondary phases MgO (~10 mass%) and Eu2 O3 (<0.5 mass%). The photoluminescence spectra of the doped spinel nanopowders show an intense red emission (λem = 615 nm) resulting from the 5 D0 → 7 F2 transition with a maximum intensity at an excitation wavelength of 470 nm.